Congenital Callosal Defects - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A lethal and previously undescribed syndrome in 3 siblings with hypoplasia of the corpus callosum is described from the Istituto Materno-Infantil de Pernambuco, and Laboratorio de Genetica, Universidade Federal de Pernambuco, Recife, PE, Brazil.